The daily reader for contemplative living : excerpts from the works of Father Thomas Keating, O.C.S.O. : sacred scripture, and other spiritual writings /: excerpts from the works of Father Thomas Keating, O.C.S.O. : sacred scripture, and other spiritual writings. (2013 copyright 2013) - Unknown
No abstract available